Profitability, CSR, Institutional Ownership, and Independent Commissioners’ Effect on Firm Value in the Indonesian Food and Beverage Sector - Muhammad Dhani Raharja; Roy Budiharjo (AIBPM Publisher, 2026)
The volatility of firm value in the defensive food and beverage (FB) industry remains a significant concern for investors, exacerbated by inconsistent findings in prior research. This study aims to investigate the impact of profitability (ROA), corporate social responsibility (CSR), institutional ownership, and independent commissioners on firm value (Tobin’s Q) within the FB sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. 15 businesses were chosen via purposive sampling in a quantitative manner, and panel data regression utilizing the FEM was used for analysis. The numerical results demonstrate that while the variables simultaneously affect firm value significantly (F-statistic = 100.70; p 0.05), partially, profitability (p = 0.0892), CSR (p = 0.1968), and independent commissioners (p = 0.2603) show no significant impact. Conversely, institutional ownership has a substantial negative impact (b = -13.475; p = 0.0000). These findings imply that investor valuation in the post-pandemic era is driven by concerns over institutional dominance and market sentiment rather than traditional financial metrics. This research provides updated empirical evidence to bridge theoretical gaps regarding valuation determinants in defensive sectors.